THE DIFFERENCES BETWEEN STUDENTS' WRITING NARRATIVE WITH COOPERATIVE LEARNING MODEL OF CIRC AND JIGSAW BY CONSIDERING MOTIVATION OF CLASS VII SMP NEGERI 28 PADANG - Yudha, Nicky Prima; Ramadhan, Syahrul; Manaf, Ngusman Abdul (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2014)
This study was conducted to explain (a) the difference in narrative essay writing skills of students who are taught using cooperative learning model CIRC with Jigsaw (b) differences in the ability to write narrative essays highly motivated students who are learning with cooperative learning model CIRC with Jigsaw; (c) differences in the ability to write narrative essays low motivated students who are learning to cooperative learning model CIRC with Jigsaw; and (d) the interaction between the use of models in the study of learning and motivation affect the ability of students to write a narrative essay. This study was a quasi-experimental (quasi-experiment) using a 2x2 factorial design. Population of 250 people, the study sample is taken by means of random sampling and obtained class VII / 2 as an experimental class I and class VII / 1 as the experimental class II, each consisting of 30 and 32 students. Data were collected by two instruments, namely motivation questionnaire and performance test writing narrative essays. Analyzing and discussion of the data is done by descriptive-analytical. Based on the results of data analysis, we can conclude the following four things. First, there are no significant differences in narrative essay writing skills of students who are taught using cooperative learning model CIRC with Jigsaw. Secondly, there is no significant difference in the ability to write narrative kararangan highly motivated students who are learning with cooperative learning model CIRC and Jigsaw. Third, there is no significant difference in the ability to write narrative kararangan low motivated students who are learning to cooperative learning model CIRC and Jigsaw. Fourth, there is no interaction between the model of learning with learning motivation in influencing the ability to write narrative essays seventh grade students of SMP Negeri 28 Padang. The use of models and Jigsaw cooperative CIRC can enhance students' ability to write a narrative essay, motivated either high or low.